Scale and access issues affecting smallholder hog producers in an expanding peri-urban market: Southern Luzon, Philippines - Costales, Achilles; Delgado, Christopher L.; Catelo, Maria Angeles O.; Lapar, Ma. Lucila; Tiongco, Marites; Ehui, Simeon; Bautista, Anne Zillah (International Food Policy Research Institute, 2007)
A dramatic increase over the past fifteen years in domestic pork demand and production in the Philippines has created a potentially profitable opportunity for poor rural and agricultural households. In Southern and Central Luzon, the two biggest markets, however, smallholder pig producers hold only a minority share of total production compared to larger commercial farms. This report seeks to assess the scope for smallholders to remain in business by analyzing the relative profitability of small and large farms. Using field data from pig-producing households, the researchers assess the role of internal and external factors in determining a household's participation in production and marketing and examine the combination of technical and allocative efficiency exhibited by specific farms under particular circumstances. They conclude that the smallest-scale pig producers will not survive market competition and will require alternative occupations. Many others, however, could profit from pig production if policy and institutional changes ensure their access to inputs, to animal health services that can guarantee output quality, and to markets for higher quality output. These findings are a valuable contribution to poverty reduction efforts in the Philippines.